SCREENING OF ANTIBACTERIAL ACTIVITY OF CRUDE LEAF EXTRACTS OF CASSIA TORA ON UTI PATHOGENS - SAHU , PINKI RAJ; M. P. SINHA (The Bioscan, 2013)
Antibacterial effect of crude methanolic and aqueous extracts of leaves of Cassia tora against pathogenic bacteria E. coli, P. aeruginosa, S. aureus and K. pneumoniae isolated from patients of U.T.I, were investigated using agar well diffusion method. Among the various concentration tested (ranging from 0.0625 to 6.0 mg/mL), 1.0 -2.0 mg/ mL of methanolic extract was found to be the minimum inhibitory concentration (MIC) for almost all the test organisms while aqueous extract showed MIC at > 6.0 mg/mL. P. aeruginosa and K. pneumoniae were resistant to aqueous extract. Methanolic extract was more effective over aqueous extract producing larger zone of inhibition ranging between 12-24mm. The traditional claims of leaves of C. tora as an antibacterial ability have been confirmed as the extracts displayed activity against the pathogens associated with UTI. This study indicates that the leaves of C. tora can be used as a source for new broad spectrum oral drug.